Pengujian Prestasi Kincir Air Tipe Overshot Di Irigasi Kampus Universitas Riau Dengan Penstock Bervariasi - T Harismandri; Asral Asral (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Currently the electricity has became a major requirement for human life. To fulfill the needs of electricity, the society used normally rely on state power generation company. Besides, that seemingly to electricity can be generated by means of utilizing the potential of natural energy that is around us. One untapped sources of the potential energy is energy of water, which in reservoirs of an environment campus of the University of Riau. According surveys, reservoir’s Riau University has head of 0.7 m and flow of 0.02 m3/s. This data used as a basis data to design type of overshot waterwheel. The waterwheel was tested by varying the penstock shape i.e cylindrical and rectangular. Based on design method was produced the diameter of waterwheel, the number and size of the blades as well as the sizes of penstock. The outside diameter and inside of wheel were 0.6 m and 0.5 m. Number of blades were 18 pieces with an area of 0,01m2. Then, the cylindrical penstock has 0.089 m of the diameter, whereas rectangular penstock sized of 0.1 m of wide and 0.1 m of high. Maximum power output was generated by the waterwheel with a cylindrical penstock of 21.05 Watt and efficiency of 43.78%, while for rectangular penstock was indicated the maximum power output of 19.8 Watts and efficiency of 42.40%.Keywords : PLTPH, Design of Water Wheel, Penstock